Boron‐doped Diamond Electrodes Modified with Fe3O4@Au Magnetic Nanocomposites as Sensitive Platform for Detection of a Cancer Biomarker, Interleukin‐8. Issue 8 (4th March 2016) - Braiek, Mohamed; Yang, Yi; Farre, Carole; Chaix, Carole; Bessueille, François; Baraket, Abdoullatif; Errachid, Abdelhamid; Zhang, Aidong; Jaffrezic‐Renault, Nicole
Abstract: Interleukin‐8 (IL‐8), a dimeric protein composed of two identical subunits, is overexpressed in different human cancers, among them pancreatic cancers and head and neck cancers. There is a strong demand for monitoring of this biomarker protein for early cancer detection. A new concept of label‐free impedimetric immunosensors for IL‐8 detection is described in this work. A nanocomposite of gold nanoparticles (AuNPs) decorating a magnetic Fe3 O4 core is synthesized using cysteamine as linker, and characterized using TEM and UV‐Vis spectrometry. After immobilization of these Fe3 O4 @Au magnetic nanocomposites on a boron doped diamond (BDD) electrode using a simple magnet, anti‐human IL‐8 monoclonal antibody is linked to the AuNPs, previously functionalized with thioctic acid. The functionalization of the immunosensor was characterized using two electrochemical techniques: cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS), performed in phosphate buffer with ferro/ferricyanide as the redox probe. The EIS technique was used for affinity assays: antibody‐Antigen binding. A linear relationship between the increment in the electron transfer resistance (RCT ) and the logarithmic value of IL‐8 concentration was observed between 0.1 pg/mL and 1000 pg/mL. The limit of detection (LOD) was estimated at 0.03 pg/mL. Abstract :